Structural, optical and elastic properties of silver oxide incorporated zinc tellurite glass system doped with Sm3+ ions - .A., Tafida R.; M. K., Halimah; F. D., Muhammad; K.T., Chan; M. Y., Onimisi; A. D., Usman; A. M., Hamza; S. A., Umar (Elsevier BV, 2020)
Zinc tellurite glasses in the form of [{(TeO2)0.7 (ZnO) 0.3}0.99 (Sm2O3)0.01]1-y (Ag2O) y, y = 0.005. 0.01, 0.015, 0.02 and 0.025 M fraction is prepared by the method of melt quenching. The molar volume decreases while the density of the glasses increases with an increase in dopant. The indirect and direct band gap increased with an increase in dopant content. Urbach energy, molar refraction, molar polarizability, refractive index, and electronic polarizability are shown to be decreased with an addition of silver oxide. The samples shear and longitudinal velocities are measured at room temperature of 5 MHz frequency. Poisson ratio (σ), Elastic moduli, hardness (H), Debye temperature ( ), Softening temperature ( ), bond connectivity (d) and fugacity ( ) are calculated to reveal the quantitative analysis concerning the structure of the synthesized glasses. The obtained results have revealed the adverse effect of silver oxide on the host materials by enhancing the properties and strengthening the glass network.